2017
DOI: 10.20870/oeno-one.2016.0.0.1619
|View full text |Cite
|
Sign up to set email alerts
|

Issues to be considered for strategic adaptation to climate evolution – is atmospheric evaporative demand changing?

Abstract: The predicted developments in climate are region-specific and adaptation can only be successful considering the regional characteristics with its diverse technical, environmental, economic and social implications. Beyond some obvious adaptation strategies in response to emerging environmental constraints for example there are many more "basic" challenges below "the surface". One of the key concerns for many regions is the availability of water and how increasing temperature will drive the evaporative demand of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
0
8
0
2
Order By: Relevance
“…These results are consistent with the Mediterranean climate of the study zone that Schultz (2017) characterized as a waterlimited region. According to Schultz (2017), during the summer period, water constraints appear progressively because the evaporative demand largely exceeds precipitation. These results were also consistent with other research that have studied the shoot growth stop when the vine is exposed to water restriction, in both experimental (Pellegrino et al 2005) and real conditions (Martinez-De-Toda et al 2010) The results here also indicated that the shoot growth stop was earlier in the 2020 season.…”
Section: Apex-vigne Application Adoption -Location Of Surveysmentioning
confidence: 99%
“…These results are consistent with the Mediterranean climate of the study zone that Schultz (2017) characterized as a waterlimited region. According to Schultz (2017), during the summer period, water constraints appear progressively because the evaporative demand largely exceeds precipitation. These results were also consistent with other research that have studied the shoot growth stop when the vine is exposed to water restriction, in both experimental (Pellegrino et al 2005) and real conditions (Martinez-De-Toda et al 2010) The results here also indicated that the shoot growth stop was earlier in the 2020 season.…”
Section: Apex-vigne Application Adoption -Location Of Surveysmentioning
confidence: 99%
“…Climate changes may have dramatic effects on viticulture and wine industry, maintenance of landscape, and promotion of tourism (Hannah et al 2013). However, the predicted changes of climate are region-specific and adaptation can only be successful considering the regional characteristics with its diverse technical, environmental, economic, and social implications (Schultz 2017). Predicting precisely the impact of climate change on viticulture is difficult for several reasons (a) there are uncertainties on the outputs of the predictive models; (b) models should be adapted to viticulture and should be considered on a small scale (plot or terroir) rather than on a regional scale, because microclimate (altitude, slope, orientation of the vine rows) and soil heterogeneity significantly change the scenario predicted at the larger scale (Quénol et al 2017).…”
Section: Ongoing and Expected Effects Of Climate Changementioning
confidence: 99%
“…The evolution of the atmospheric water demand is a matter of debate. Using formulas such as Penman-Montheith's, evapotranspiration (ET) are supposed to increase together with temperatures but trends for decrease in pan evaporation were also reported (Roderick et al 2009;Schultz 2017). The opinion that water deficit will increase in the future is nevertheless widely shared.…”
Section: Water Use Efficiencymentioning
confidence: 99%
“…The evolution of atmospheric water demand is a matter of debate. Using computational methods such as the Penman-Monteith-FAO equation, the evapotranspiration (ET) is believed to increase together with temperatures but trends for a decrease in pan evaporation were also reported ( Roderick et al, 2009 ; Schultz, 2017 ). The opinion that the water deficit will increase in the future is nevertheless widely shared.…”
Section: Introductionmentioning
confidence: 99%